Parent Language Input Prior to School Forecasts Change in Children’s Language-Related Cortical Structures During Mid-Adolescence - Demir-Lira, Ö. Ece; Asaridou, Salomi S.; Nolte, Collin; Small, Steven L.; Goldin-Meadow, Susan (Frontiers in Human Neuroscience, 2021)
Children differ widely in their early language development, and this variability has important implications for later life outcomes. Parent language input is a strong experiential factor predicting the variability in children’s early language skills. However, little is known about the brain or cognitive mechanisms that underlie the relationship. In addressing this gap, we used longitudinal data spanning 15 years to examine the role of early parental language input that children receive during preschool years in the development of brain structures that support language processing during school years. Using naturalistic parent-child interactions, we measured parental language input (amount and complexity) to children between the ages of 18 and 42 months (n = 23). We then assessed longitudinal changes in children’s cortical thickness measured at five time points between 9 and 16 years of age. We focused on specific regions of interest that have been shown to play a role in language processing. Our results support the view that, even after accounting for important covariates such as parental IQ and education, the amount and complexity of language input to a young child prior to school forecasts the rate of change in cortical thickness during the 7-year period from 5½ to 12½ years later. Examining the proximal correlates of change in brain and cognitive differences has the potential to inform targets for effective prevention and intervention strategies.